Gramática fundamental del español - Moreno Fernández, Francisco; Penadés Martínez, Inmaculada; Ureña Tormo, Clara (Routledge introductions to Spanish language and linguistics, 2020)
"Gramática fundamental del español covers a wide range of topics related to basic Spanish grammar. Using contextualized examples and a cognitive approach, it presents different ways of understanding diverse basic aspects of grammar usage and meaning, including: phrases, clauses and sentences word classes and sentence patterns parsing and diagramming in sentence analysis grammar of the word and grammar and writing Also provided are a Glossary of grammar terms, an Appendix with a list of sentential schemes, solutions to exercises, and an Analytical Index. This is key reading for learners of Spanish and Hispanic Studies at ACTFL level intermediate-low to advanced-high (CEFR B1 - C2)"--